Medicinal use of marijuana and its impacts on respiratory system - Sajedeh Rabipour; Evan Abdulkareem Mahmood; Maryam Afsharkhas (Journal of Chemistry Letters)
Marijuana use has increased in Chile in recent years, especially among young people and adolescents, and there seems to be a general perception that its use does not entail greater risks. The current discussion on the legalization of marijuana must make the necessary distinction between medicinal use and recreational use of it. There are few indications approved by international health organizations for its medicinal use, all of them with synthetic derivatives for oral administration, and countless other indications based mostly on studies that suffer from serious methodological deficiencies. The recreational use of marijuana, in addition to the widely known deleterious psychosocial effects, induces the appearance of chronic airway symptoms, local inflammation and immunomodulatory effects on the respiratory system and, depending on the time and amount of exposure, has been associated with adverse effects. negative on lung function, development of COPD and lung cancer. Therefore, the unrestricted recreational use of this drug could have a great unfavorable impact on personal and public health in the future, so the free consumption of marijuana should not be recommended.